On Covidiots and Covexperts: Stupidity and the Politics of Health - Tom Grimwood (University of Calgary, 2021)
The COVID-19 pandemic has highlighted the significance of the politics of health as an ongoing interpretative event. The effectiveness of delivering prevention strategies is in negotiation with day-to-day arguments in the public sphere, not just by “experts” in peer-reviewed papers, but also in the everyday interpretations and discussions of available expertise on print and digital media platforms. In this paper I explore ae particular facet of these public debate over the politics of health: the deployment of the commonplace of stupidity. I argue that the growth of this commonplace within discussion is rooted in particular models of interpretation which limit self-understanding, by over-emphasising certain points of significance within the interpretative horizon over more banal (and “stupid”) aspects that are, nevertheless, influential on health interventions.